Analisis Pelanggaran Hak Ekonomi Lagu Akad Karya Payung Teduh dalam Penggunaan Kepentingan Komersial - Gina Sonia Kafiar; Ni Komang Irma Adi Sukmaningsih (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
Copyright is a key pillar of the Intellectual Property Rights system, providing legal protection for creative works in the arts sector, particularly musical works. Within the copyright framework, the most crucial aspect is economic rights, namely the exclusive right of creators to derive financial benefit from any use of their works. However, the reality on the ground demonstrates the rampant use of songs for commercial purposes without proper authorization, which directly harms creators. This article analyzes economic rights violations in the context of commercial use, using the case study of the song "Akad" by Payung Teduh as a case study. This research uses normative legal methods through a statutory and legal conceptual approach. The research findings indicate that the exploitation of songs for material gain without the explicit consent of the rights holder constitutes a clear violation of Law Number 28 of 2014 concerning Copyright. Such violations carry serious legal consequences, including civil liability in the form of compensation payments and criminal sanctions. Therefore, synergy between firm law enforcement and increased collective public awareness is necessary. These efforts are vital to guaranteeing the protection of creators' economic rights while creating a healthy, fair, and sustainable creative industry ecosystem in Indonesia for all arts stakeholders.